2022
DOI: 10.1007/s13593-022-00814-3
|View full text |Cite
|
Sign up to set email alerts
|

Gendered perception of change in prevalence of pests and management in Zimbabwe smallholder irrigation schemes

Abstract: A better understanding of gendered perception on the prevalence and management of pests in irrigated agriculture in the context of a changing climate can help recommend more gender-sensitive policies, particularly in smallholder farming systems. Limited studies have been conducted to assess gender differences in perception of the prevalence and management of pests among smallholder irrigation schemes especially in Zimbabwe. This study is the first one to assess gendered perceptions on the change in prevalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
(54 reference statements)
0
0
0
Order By: Relevance
“…Women are known to take leadership roles in pesticide application in some developing countries; however, in this study, pesticides were mainly applied by men. This is because women had knowledge of the possible negative effects of pesticide use, as well as alternative pest control measures and beneficial insects, despite their ability to observe the change in prevalence of pests [34]. The study found that age was negatively associated with the probability of choosing integrated pest management methods.…”
Section: Discussionmentioning
confidence: 95%
“…Women are known to take leadership roles in pesticide application in some developing countries; however, in this study, pesticides were mainly applied by men. This is because women had knowledge of the possible negative effects of pesticide use, as well as alternative pest control measures and beneficial insects, despite their ability to observe the change in prevalence of pests [34]. The study found that age was negatively associated with the probability of choosing integrated pest management methods.…”
Section: Discussionmentioning
confidence: 95%
“…Bunds also aid in the growth of vegetation because they trap grass and shrub seeds, preserving plant diversification and increasing the food and wood fuel available to smallholder farmers. The bunds have indeed, in countries such as Niger and the Central Plateau of Burkina Faso, not only helped to increase yields for cereals such as sorghum but also have [61] fostered the increase in groundwater levels that have helped farmers start growing vegetables on small plots nearer to water sources such as wells-leading to improvement in both their incomes and diversified diets [54], while as well reducing GHG emissions [4,32].…”
Section: Cs-ipm Knowledge Pest Preventions and Water Management Pract...mentioning
confidence: 99%
“…According to Liboster's assessment of the gendered perspective of changes in pest prevalence and management in Zimbabwe, farmers' perceptions of these changes vary by gender [61]. Gender perception of change in the prevalence of pests can be a valuable resource for the sustainable development of smallholder irrigation farming systems and scientific research [9].…”
Section: Cs-ipm Knowledge Pest Preventions and Water Management Pract...mentioning
confidence: 99%
See 1 more Smart Citation